2020
DOI: 10.1128/jb.00138-20
|View full text |Cite
|
Sign up to set email alerts
|

Two Ways To Convert a Low-Affinity Potassium Channel to High Affinity: Control of Bacillus subtilis KtrCD by Glutamate

Abstract: Potassium and glutamate are the major cation and anion, respectively, in every living cell. Due to the high concentrations of both ions, the cytoplasm of all cells can be regarded as a potassium glutamate solution. This implies that the concentrations of both ions need to be balanced. While the control of potassium uptake by glutamate is well established for eukaryotic cells, much less is known about the mechanisms that link potassium homeostasis to glutamate availability in bacteria. Here, we have discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…5B), however, the mechanism responsible for this control has yet to be uncovered. We have previously demonstrated that a potassium channel (KtrCD) is directly activated and thus converted from a low-to a high-affinity uptake system in the presence of glutamate [41]. Here, we show that similarly the affinity of the high affinity glutamate transporter GltT is controlled by the presence of potassium: At high potassium concentrations, the affinity of GltT for glutamate is increased fivefold.…”
Section: Aima (Ybec) Is a Novel Major Glutamate Transportermentioning
confidence: 68%
See 4 more Smart Citations
“…5B), however, the mechanism responsible for this control has yet to be uncovered. We have previously demonstrated that a potassium channel (KtrCD) is directly activated and thus converted from a low-to a high-affinity uptake system in the presence of glutamate [41]. Here, we show that similarly the affinity of the high affinity glutamate transporter GltT is controlled by the presence of potassium: At high potassium concentrations, the affinity of GltT for glutamate is increased fivefold.…”
Section: Aima (Ybec) Is a Novel Major Glutamate Transportermentioning
confidence: 68%
“…A B. subtilis strain lacking all three diadenylate cyclases is unable to grow at potassium concentrations of 5 mM or higher or in the presence of glutamate (even at low potassium concentrations) [21,41]. In order to get more comprehensive insights into the toxicity of glutamate for the c-di-AMP-free strain GP2222 (designated Δdac from here on), we decided to isolate and study a larger set of suppressor mutants that tolerate the presence of glutamate.…”
Section: Growth Of a Strain Lacking C-di-amp In The Presence Of Glutamentioning
confidence: 99%
See 3 more Smart Citations